A new intuitional algorithm for solving heterogeneous fixed fleet routing problems: Passenger pickup algorithm - Gencer, Cevriye; Top, İsmail; Aydogan, Emel Kizilkaya (Applied mathematics and computation, 2006)
Fixed-fleet heterogeneous vehicle routing is a type of vehicle routing problem that aims to provide service to a specific customer group with minimum cost, with a limited number of vehicles with different capacities. In this study, a new intuitional algorithm, which can divide the demands at the stops for fixed heterogeneous vehicle routing, is developed and tested on tests samples. The algorithm is compared to the BATA Algorithm available in the literature in relation to the number of vehicles, fixed cost, variable cost and total cost.